The Relationship Between the Mental Revolution and Legal Products in Jokowi's First Term - Musmulyadin Musmulyadin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Jokowi's big vision regarding mental revolution has a historical background in the era of President Ir. Sukarno. The structuring of the nation's mentality has had a correlation in the past with the development of the nation's character (nation and character building). Jokowi personally has shown practice and discipline in serving the community. However, is Jokowi's behavior automatically followed by state/bureaucratic administrators? Continuity between Jokowi's behavior and bureaucratic behavior that must be implemented as a part of providing services to the community. Jokowi as the holder of the people's mandate through elections must be able to present a legal basis in ensuring the implementation of the vision, mission and action program. The research method used is qualitative with a legal/legal approach, an ethical approach and a hermeneutical approach to related legal texts. The mental revolution has become a national movement with the presence of